(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
There is practice in the community, there is often a discrepancy between the laws and regulations and their implementation. The Underwriting Right is not registered at the Land Office, this raises a problem with the Underwriting Rights which if it is not registered at the land office, the Underwriting Right will not get the Underwriting Certificate, the Underwriting Certificate issued by the land office and this certificate is proof from the existence of Underwriting Rights, in addition, also often the registration of Underwriting Rights is carried out late from the period specified by the Act. In essence, the community must comply with the prevailing laws and regulations so that problems do not occur in the future. Underwriting rights in the form of land and buildings are inseparable from the Agrarian regulations which the mechanism for registration of Underwriting Rights is carried out at the land office on the basis of data in the APHT issued by PPAT with a book of Mortgage Rights. The form and content of the Underwriting Rights book have been stipulated based on Agrarian Minister Regulation number 3 of 1997. The Deed of Granting Mortgage (APHT) regulates the terms and conditions regarding the granting of the Underwriting Right from the Debtor to the creditor in connection with the debt pledged as a Mortgage Right. The granting of this right is intended to give the priority position to the creditor concerned, so the granting of the Underwriting Right is a guarantee of repayment of the debt to the creditor in connection with the loan or credit agreement in question.